Thermal history and parental magma composition of early olivine gabbros of the Troodos ophiolite, Cyprus - Hu, Wen-Jun; Zhou, Mei-Fu; Malpas, John; Wang, Zhenchao (Lithos, 2022)
Samples of an early olivine gabbro in the lower plutonic sequence of the Troodos ophiolite were studied to constrain their thermal history and the compositions of their parental magma. These rocks exhibit typical orthocumulate textures and petrographic evidence of reaction between a migrating interstitial magma and a crystal mush, including embayed margins of olivine crystals and irregular ragged grain boundaries of clinopyroxenes, indicating dissolution of olivine and crystallization of clinopyroxene, followed by crystallization of plagioclase within the framework of olivine and clinopyroxene. All the minerals exhibit relatively homogeneous compositions, without any clear zoning in either their major or trace elements, indicating that the minerals and migrating magma reached equilibrium. The rare earth element (REE) distribution between clinopyroxene and plagioclase records an equilibrium temperature of about 1300 °C, but the Mg-exchange geothermometer yielded a lower temperature of about 1000 °C. These different closure temperatures indicate a rapid cooling history with a cooling rate of −2 °C/year log units. The low TiO2 contents and additional trace element compositions of clinopyroxene show that the parental magma of the gabbro was related to boninitic magmas of the ophiolite. Consequently, we show that some boninitic lavas in the upper oceanic crust have been affected by melt-rock reaction process during their ascent through the lower crust, and therefore their composition cannot be directly used to constrain the composition of the primary boninites. •Gabbros of the Troodos ophiolite display petrographic evidence of reaction between a migrating magma and a crystal mush.•Trace elements of clinopyroxene indicate that the migrating magma is related to boninites in the UPL.•Some boninitic lavas affected by melt-rock reaction process cannot represent composition of the primary boninite.